Unraveling phytochemicals with potential therapeutic application for neurodegeneration - Vaz, Marcela Tatiana Barros (2020)
"Epidemiological data suggest that phytochemicals may prevent and even reverse specific pathological processes underlying neurodegenerative diseases. A (poly)phenol-enriched fraction from leaves of Corema album was previously reported to modulate central events related to α-Synuclein expression and aggregation as well as oxidative stress in eukaryotic models of Parkinson’s disease. In order to identify the potentially bioactive compound, this extract was subjected to a bioguided fractionation, leading to the identification of CAL_X.(...)"